The Little Data Book 2004 - World Bank (World Development Indicators, 2004)
Now in its 6th edition, The Little Data Book 2004 is a pocket-sized ready reference on key development data for 206 countries. Profiles of each country include 54 key development indicators like: Population and population growth; GNI, GDP, GDP growth, Exports and Imports, and Gross Capital Formation; Deforestation, Water Use, Energy Use and Electricity Use per Capita; Life Expectancy, Fertility Rate, Child Malnutrition, Prevalence of HIV, Girls in Primary School; Paved Roads, Aircraft Departures, Personal Computers; High-technology exports, Foreign Direct Investment, Present Value of Debt, and Aid per Capita. Drawing on data from the World Bank's World Development Indicators 2004, The Little Data Book provides quick reference to the latest available data for World Bank member countries as well as other economies with populations of over 30,000. Separate tables summarize data for the World, by Region (East Asia and Pacific, Middle East and Africa, etc.), and Income Group. A helpful Glossary of Terms defines each indicator